Exfoliation-induced nanoribbon formation of poly(3,4-ethylene dioxythiophene) PEDOT between MoS2 layers as cathode material for lithium batteries - Murugan, A. Vadivel; Quintin, M.; Delville, M. H.; Campet, Guy; Gopinath, Chinnakonda S.; Vijayamohanan, K. (Journal of Power Sources, 2006)
A new type of layered nanocomposite synthesized by delaminated MoS2 nanosheets and poly(3,4-ethylenedioxythiophene) (PEDOT) are restacked to produce alternate polymer nanoribbons between layers Of MoS2 with an interlayer distance of similar to 1.38 nm. The unique properties of resulting nanocomposite are investigated by powder XRD, XPS, SEM, TEM, and four-probe conductivity measurements. The obtained nanocomposite can be used as a cathode material for a small power rechargeable lithium battery as demonstrated by the electrochemical insertion of lithium into the PEDOT/MoS2 nanocomposite. A significant enhancement in the discharge capacity (100 mAh g(-1)) is observed compared with that (40 mAh g(-1)) for MoS2. (c) 2005 Elsevier B.V All rights reserved.
Keywords: cathode material; lithium batteries; MoS2; organic-inorganic nanocomposite; PEDOT-nanoribbons